“Deshidratación por aire caliente de musculo de camarón gigante de malasia (macrobruchium rosenbergii)” - Díaz Viteri, Javier Eduardo (2003)
factor involved in controlled muscle of shrimp drying permits process optimisation and assists in design of suitable dryers. The study undertook two stages: first a thermal pre-treatment submerging the whole shrimp in water at 90ºC for 90 seconds, were the orange colour and textura was improved. Was used then the sample underwent osmotic dehydration in ternary solution of 20% suerosa and 20%of NaCI ( % weight) under agitation at 120 rpm for 30 minutes to temperatura of 20ºC. The second stage was the drying where the experimental curves were obtained in laboratory dryer under different drying conditions from 40, 50 and 60ºC , and air velocity from 0.5, 0.8 and 1.1 m/s. during this whole process the time of drying was controlled at regular time in someway, the loss weight produced by the evaporation of water contained in the muscle was controlled. With this parameter the product was obtained sensorily acceptable, determination carried out by means of affective test. The mass transfer phenomena during in shrimp muscle are always based on Fick's second law, and solved for the infinita cylinder without considering the shrinkage for evaluation constant effective diffusivity. Moisture diffusivity was calculated adjust using the program Microcal Origin 3.0, being determining a degree of reasonably good adjustment, as for the coefficient of moisture diffusion. lts value is increased from 1.81 x 10 -10 m2 /s up to 7.7 x 10-10 m2/s when the temperatura is increased from 40°C to 60ºC. The adsorption isotherms in muscle of giant shrimp previously pretreatment described up lines were determinad using gravimetric static method. Experiments at three temperatura levels: 40ºC, 500C and 60 °C, and seven water activity levet from O. 11 to 0.89 were carried out. Along with five well known models, Chung - Pfost, Gab, Halsey, Oswin and Bet has been applied to fit the data to calculated the isisoteric heat of adsorption determination. Other determinations like the proximal content of muscle of giant shrimp were also carried where humidity 79.19%, protein content 18.55%, fat content 1.03% and ash content 1.53 % for fresh sample of shrimp. The analysis proximal for shrimp dehydrated were humidity 8.00%, protein content 81.10, fat content 4.10 and ash cont